Pareceristas deste volume - tempos, outros (Outros Tempos: Pesquisa em Foco - História, 2010)
Adriana Maria de Souza Zierer (UEMA); Adroaldo José Silva Almeida (IFMA); Alina Silva Sousa (UFMA); Alômia Abrantes da Silva (UEPB); André Roberto de Arruda Machado (Almanack Braziliense/USP); Antônia da Silva Mota (UFMA); Carlos Alberto Ximendes (UEMA); Constância Lima Duarte (UFMG); Cristina Scheibe Wolff (UFSC); Elizabeth Sousa Abrantes (UEMA); Elizangela Barbosa Cardoso (UFPI); Gamaliel Carreiro (UFMA); Helidacy Maria Muniz Corrêa (UEMA); Ilma Fátima de Jesus (Faculdade Santa Fé); Iran de Maria Leitão Nunes (UFMA); Irenilda Barreto de Rangel Moreira Cavalcanti (FEAP); João Bittencourt (UFMA); José Henrique de Paula Borralho (UEMA); Josenildo de Jesus Pereira (UFMA); Juciana de Oliveira Sampaio (IFMA); Júlia Constança Pereira Camêlo (UEMA); Lourdes de Maria Leitão Nunes Rocha (UFMA); Marcelo Cheche Galves (UEMA); Márcia Maria da Silva Barreiros Leite (UEFS); Márcia Milena Galdez Ferreira (UEMA); Marivânia Furtado (UEMA); Olívia Candeia Lima Rocha (UFPI); Paulo Roberto Rios Ribeiro (Faculdade São Luís); Régia Agostinho da Silva (UFMA); Reinaldo dos Santos Barroso Júnior (UEMA); Rogério de Carvalho Veras (UEMA); Rosângela de Sousa Veras (IFMA); Sandra Maria Nascimento (UFMA); Sandra Regina Rodrigues dos Santos (UEMA); Sônia Cristina da Fonseca Machado Lino (UFJF); Sônia Maria de Meneses Silva (URCA); Tânia Salgado Pimenta (FIOCRUZ); Teodora Torres (UNICEUMA); Vivian Aranha Sabóia (UEMA); Wandeilson Miranda (UFMA); Yuri Michael Pereira Costa (UEMA);